Kinematic bidimensional analysis of the propulsion technique in wheelchair rugby athletes - Sara Maria Franchin; Federico Giordani; Michele Tonellato; Michael Benazzato; Giuseppe marcolin; Paolo Sacerdoti; Francesco Bettella; Alfredo Masumeci; Nicola Petrone; Stefano Masiero (PAGEPress Publications, 2020)
Wheelchair rugby is a sport ideated for individuals with cervical spinal cord injury (CSCI) which is extremely important for maintaining their neuromuscular abilities and improving their social and psychological wellbeing. However, due to the frequent changes in direction and speed it considerably stresses the players' upper limbs. 13 athletes have undergone two sports-related tests on an inertial drum bench and several kinematic parameters have been registered. Most athletes use a semi-circular pattern which is considered protective for the upper limb. With increasing speed, range of motion (ROM) increases. Release angles increment and contact angles reduce, displacing the push angle forward to increase speed. Instead, the more anterior late push angle used to increase velocity is a factor which further loads the shoulder joint. However, other factors affecting propulsion technique, such as posture and wheelchair set up should be studied to further reduce loading on the upper limb.